On the Role of Average Values in Solving Geometric Extreme Problems - J. Husanov; N. Shamsiddinov (Researchparks Publishing, 2022)
In the article, in addition to studying the properties of functions when finding extreme values, methods for applying the average values of expressions in functions and relations between them were studied.